Linear Optical Response of a Conic Quantum Dot in the Born-Markov Regime (Orinoquia, 2021)
The linear and nonlinear optical susceptibility in a conical quantum dot (CQD) is studied theoretically. By solving a Born-Markov master equation in the Lindblad form that includes the processes of spontaneous emission and dephasing between two levels of the nanostructured quantum system. In addition, the quantum vacuum of the electromagnetic field that affects the nanostructure was considered as an environment for the system. The numerical calculations were performed for a CQD GaAs/AlGaAs. It was found that the position of the resonance peak present in the optical response as a function of incident photon energy is shifted toward regions of low energies (red shift) when the dimensions of the nanostructure are increased.
Keywords: Optical response; Born-Markov; nanostructure; quantum dot